Impact of Pulau Balang Bridge Operations on Kariangau – Penajam Ferry Service - Agusty, Cindy Lionita; Sitepu, Ganding; Idrus, Misliah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2023)
Pulau Balang Bridge is access to the Indonesia’s Capital City of IKN and connects Balikpapan to Penajam. So far, there are several alternative transportations, from the Balikpapan area to Penajam and vice versa, one of which is using a ferry, which takes 1.5 hours and added time to the queue. Another alternative is to use a speed boat, the travel time is about 15 minutes. Speed boats are only for passenger purposes and substandard safety. Currently, the number of passengers is quite significant for the Balikpapan - Penajam Ferry Service, after the Pulau Balang Bridge operation, must significantly impact the shipping industry in the Balikpapan - Penajam area. Several alternatives for transportation to connect Balikpapan - Penajam Paser Utara, which has a high annual demand for many ships. This study aims to predict the demand for the Kariangau - Penajam Ferry Service after operating the Pulau Balang bridge and determine the optimization of ships on demand for the Kariangau - Penajam Paser Utara Ferry service after the Pulau Balang bridge operates. The method used in this study is forecasting with linear regression and descriptive or survey research. Assuming there is no Pulau Balang bridge, demand for the Kariangau – Penajam ferry service for passengers grows 2% per year, two-wheeled vehicles grow 4% per year, and four-wheeled vehicles grow 1% per year. Projections of passenger demand in 2026 and 2031 are likely to be optimistic that the demand will decrease to 77% and possibly 20% pessimistic. From the distance and time of ferry service users, 7 routes (49%) of ferry service users still use the ferry line, and 5 routes (51%) of ferry service users switch to the bridge if it is already in operation. Meanwhile, from the results of direct interviews, the demand for the Kariangau - Penajam Ferry service was 23%. They would switch, 33% of respondents would take turns using ships and bridges, 20% would still use ferries, and 24% had yet needed to choose. Currently, 19 ships are operating at the Kariangau - Penajam Ferry service. For an optimistic possibility in 2026 and 2031 the demand for ships if the Pulau Balang bridge operates is 16 ships. However, for a pessimistic possibility, the ships needed to operate are only 4 ships per day.